Review of State Rating Concessions - Hancock, J; Covick, O; Abdul Halim, S; Kosturjak, A (Adelaide, 2011)
The Local Government Association of South Australia (LGA) commissioned the SA Centre for Economic Studies to undertake a review of the Rates and Land Tax Remissions scheme and other available rate relief options in order to assess their impact on ratepayers on low and fixed incomes. Section 5 of the report presents an analysis of the targeting of council rate concessions using data from Wave 9 of the HILDA dataset. A number of variables in the HILDA dataset were used to classify households as eligible or ineligible for concessions under South Australian eligibility criteria. Equivalised household income was then calculated both on a cash basis and with a more comprehensive measure including both cash income and imputed net income from dwelling ownership. The analysis suggests that the targeting of rating concessions is poor, at least if income is the relevant benchmark of needs for support. Households which are ineligible by virtue of their “renter” status but which meet other eligibility criteria receive no concession for the property rates embedded in their rents, yet they have the lowest average income of all groups considered. On the other hand there are retiree households at the very affluent end of the income distribution that are eligible for concessions.
Report commissioned by the Local Government Association of South Australia
Keywords: Income & Finance; Benefits and Payments; Housing -- Ownership; Location -- SA; Housing, communities and neighbourhoods; Income, wealth and finances; Location; Income & Finance; Housing; Benefits and Payments; Ownership; SA; Income, wealth and finances; Housing, communities and neighbourhoods